OPTIMALISASI MANAJEMEN PROYEK SISTEM INFORMASI DALAM PERSPEKTIF LITERATUR REVIEW - Ahmad Padil Rambe (Jurnal Riset Teknik Komputer, 2024)
Information system project management is a vital foundation for the operational success of companies in the current digital era. In this study, we conducted a literature review to explore the key factors influencing the effectiveness of project management. From the analysis, it was found that team skills, effective communication, and appropriate technology utilization are crucial elements contributing to project success. Strong team skills enable effective collaboration among team members, while smooth communication ensures timely and accurate information flow. Additionally, advanced technology such as project management tools provides additional benefits in terms of planning, monitoring, and reporting projects. The practical implications of these findings underscore the need for ongoing team skill development and the application of suitable technology to enhance the efficiency and success of information system projects in increasingly complex and dynamic business environments.